Single-molecule FRET studies of the cooperative and non-cooperative binding kinetics of the bacteriophage T4 single-stranded DNA binding protein (gp32) to ssDNA lattices at replication fork junctions. Issue 22 (30th September 2016) - Lee, Wonbae; Gillies, John P.; Jose, Davis; Israels, Brett A.; von Hippel, Peter H.; Marcus, Andrew H.
Abstract: Gene 32 protein (gp32) is the single-stranded (ss) DNA binding protein of the bacteriophage T4. It binds transiently and cooperatively to ssDNA sequences exposed during the DNA replication process and regulates the interactions of the other sub-assemblies of the replication complex during the replication cycle. We here use single-molecule FRET techniques to build on previous thermodynamic studies of gp32 binding to initiate studies of the dynamics of the isolated and cooperative binding of gp32 molecules within the replication complex. DNA primer/template (p/t) constructs are used as models to determine the effects of ssDNA lattice length, gp32 concentration, salt concentration, binding cooperativity and binding polarity at p/t junctions. Hidden Markov models (HMMs) and transition density plots (TDPs) are used to characterize the dynamics of the multi-step assembly pathway of gp32 at p/t junctions of differing polarity, and show that isolated gp32 molecules bind to their ssDNA targets weakly and dissociate quickly, while cooperatively bound dimeric or trimeric clusters of gp32 bind much more tightly, can 'slide' on ssDNA sequences, and exhibit binding dynamics that depend on p/t junction polarities. The potential relationships of these binding dynamics to interactions with other components of the T4 DNA replication complex are discussed.